Bioaccumulation of 2, 4, 6-trinitrotoluene (TNT) and its metabolites leaking from corroded munition in transplanted blue mussels (M. edulis). (October 2018) - Appel, Daniel; Strehse, Jennifer S.; Martin, Hans-Jörg; Maser, Edmund
Abstract: Bioaccumulation of 2, 4, 6-trinitrotoluene (TNT) and its main metabolites 2-amino-4, 6-dinitrotoluene (2-ADNT) and 4-amino-2, 6-dinitrotoluene (4-ADNT) leaking from corroded munitions at a munitions dumping site (Kolberger Heide, Germany) was evaluated in transplanted blue mussels ( Mytilus edulis ). Six moorings with mussel bags were placed east and west at varying positions near the mine mound. In order to monitor any differences resulting from changing seasons, three exposure times were chosen. First exposure period: April–July 2016 (106 days); second exposure period: July–December 2016 (146 days); third exposure period: December 2016–March 2017 (92 days). We found amounts of 4-ADNT in mussel tissue ranging from 2.40 ± 2.13 to 7.76 ± 1.97 ng/(g mussel wet weight). Neither TNT nor 2-ADNT could be detected. Considering seasonal differences, orientation and distances of the moorings to the mine mound no correlation between levels in mussel tissue was evident. Graphical abstract: Highlights: Explosives leaking from corroded munition might concentrate in marine biota. The TNT metabolite 4-ADNT accumulates in the tissue of transplanted blue mussels. Seasonal differences do not alter 4-ADNT levels in mussel tissue. Increasing distance of mussels to the mine mound did not decrease 4-ADNT levels. Explosives from corroded munition may pose a risk to human health and environment.